Sobrevivência de Xanthomonas campestris pv. campestris no solo, no filoplano e na rizosfera de plantas daninhas - Silva, João César da [UNESP] (2015)
Black rot, incited by Xanthomonas campestris pv. campestris (Xcc), is the most destructive bacterial disease of brassicas in many countries, and can promote substantial reductions in productivity. The study of survival ecological niches of phytopathogenic bacteria has great importance in the management of plant bacteriosis, since a small amount of inoculum surviving among the cultivation cycle may be sufficient to initiate a new outbreak in the field. Based on this, this study evaluated the survival of Xcc in different experiments using Xcc strain 3098C, resistant to 100 μg/mL of rifampicin. The survival of Xcc as free cells in the soil was evaluated in five experiments, carried out in field conditions, between May and August, 2014. Under controlled conditions, six types of soil were used, sampled from different areas, with or without brassicas cultivation. The colonization of phylloplane and rhizosphere of 26 weed species by Xcc was also evaluated in field experiments, between August, 2014 and October, 2015. In field experiments, Xcc survived between 4 and 7 days in the soil, being directly influenced by temperature and humidity that occurred during the experiments. Under controlled conditions, the bacteria survived for 10 to 24 days, and these periods were influenced by texture, pH and organic matter content in each soil type. In weeds rhizosphere, Xcc had low capacity to survive, at most 28 days on Raphanus raphanistrum. In phylloplane, Xcc survived more than 42 days in Lepidium virginicum, and up to 70 days in Raphanus raphanistrum. Weeds from Amaranthaceae and Poaceae families did not show potential for the epiphytic survival of Xcc.